2022
DOI: 10.3390/healthcare10081527
|View full text |Cite
|
Sign up to set email alerts
|

Healthcare Providers’ Perception and Barriers Concerning the Use of Telehealth Applications in Saudi Arabia: A Cross-Sectional Study

Abstract: Background: Telehealth services are widely used in Saudi Arabia. Despite this, neither the use rate nor the attitudes, perceptions, and barriers concerning telehealth applications have been evaluated nationally from the perspective of healthcare providers (HCPs). Aim: This study aims to explore the use rate of telehealth, as well as the attitudes, perceptions, and barriers concerning telehealth use in Saudi Arabia from the perspective of HCPs. Methods and design: A cross-sectional survey was conducted and dist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 38 publications
(45 reference statements)
2
8
0
Order By: Relevance
“…While the majority of the participants had never heard about digital health, their major source of information was the Internet, and less health worker communication. Similarly, other studies have indicated that even among health workers, medical app utilization is low due to personal reasons [24]. Some health workers are still locked up in the traditional life of no smart devices, and even when they obtain smart devices, they are not interested in the functioning of the medical apps on such devices.…”
Section: Discussionmentioning
confidence: 99%
“…While the majority of the participants had never heard about digital health, their major source of information was the Internet, and less health worker communication. Similarly, other studies have indicated that even among health workers, medical app utilization is low due to personal reasons [24]. Some health workers are still locked up in the traditional life of no smart devices, and even when they obtain smart devices, they are not interested in the functioning of the medical apps on such devices.…”
Section: Discussionmentioning
confidence: 99%
“…The respondents had not much knowledge of the asked subject areas. Contrastingly, other studies have indicated that even among health workers, medical app utilization is low due to personal reasons [21]. Some people are still locked up in the traditional life of no smart devices and even when they get smart devices they are not interested in the functioning of the medical apps on such devices.…”
Section: Difficulty In Downloading App and Using Itmentioning
confidence: 92%
“…Recent studies have investigated the potential use of telemedicine services in Saudi Arabia. Alghamdi et al assessed healthcare providers’ perspectives on telemedicine during the COVID-19 pandemic, finding moderate to high levels of readiness ( 21 ). AlBar et al studied patients’ acceptance of eHealth services, noting the significant influence of perceived usefulness and ease of use on attitudes.…”
Section: Introductionmentioning
confidence: 99%